Massive Pericardial Effusion – An Uncommon Initial Presentation in aMale Patient With Systemic Lupus Erythematosus - Vivek Kumar (Indonesian Rheumatology Associantion, 2024)
Systemic lupus erythematosus (SLE) is an autoimmune disease whichhas predilection for female gender. Usually, it manifests as myriad ofclinical signs and symptoms which can involve any organ system of thebody, however cardiovascular involvement solely as an initialpresentation is uncommon. Here we present a case of a male patientwho initially presented with a large pericardial effusion. Later, onextensive workup he was diagnosed with SLE with lupus nephritis.